Analysis of Vegetation Density and Distribution of Green Belts in the City Center of Medan Using the Normalized Difference Vegetation Index - Nur Hidayat; Anita Zaitunah; Nelly Anna; Samsuri; Evalina Herawati; Alfan Gunawan Ahmad (Journal of Sylva Indonesiana, 2026)
This study evaluates the distribution and condition of vegetation within the green belts of Medan City Center in 2025 by employing the Normalized Difference Vegetation Index (NDVI) derived from Sentinel-2 satellite imagery, supplemented by field verification through purposive sampling. The analysis reveals that the findings indicate that non-vegetated category (NDVI < 0.1) dominated, encompassing 12,240.98 hectares or approximately 43.98%, whereas the dense vegetation class (NDVI 0.3–0.4) represents the smallest portion, covering only 3,009.70 hectares (10.81%) of the total area.Vegetation index values within these urban corridors range from a maximum of 0.55 to a minimum of -0.04, where lower values are predominantly associated with built-up areas and open land, while higher values are restricted to riparian buffers and fragmented green spaces. Spatial pattern analysis, utilizing a 500-meter buffer, highlights significant disparities in vegetation distribution and underscores the mounting pressure of urbanization, which has compromised the ecological functions of the city’s green infrastructure. Consequently, these findings emphasize the critical need for strategic planning and robust policy interventions to revitalize green open spaces as essential ecological infrastructure; therefore, the primary recommendation focuses on expanding green belt vegetation through intensification and protection efforts to ensure that ecological, social, and aesthetic functions are maintained sustainably within the Medan City Center.